A inserção do invisibilizado: um estudo sobre o ensino de língua portuguesa à criança haitiana e a gestão de línguas na educação básica em Medianeira - Paraná - Santos, Rosane Aparecida Biterlini dos (2019)
Situated in the contexto of thehuman sciences, specifically Applied Linguistics, this research try to answer the following question: it is possible to comply with the educational needs of Haitian students living in the city of Medianeira-PR, inserted in a context of a monolingual perspective, where they speak, read and write only in Portuguese? If possible, how can this happen both through language management and through specific work with the languages involved, understood as multilingual practices? The research is justified by the fact that there is growing Haitian immigration in Brazil and the need for schooling of the children of these immigrants, which, because they don’t know the language and are inserted in a supposedly monolingual educational context, become invisible. Thus, this research has for objective to describe and evaluate the teaching-learning proposal and the management of the Portuguese language to the Haitian child.This is a qualitative research, formatted as action research, as it enables the researcher's planned participation in the situation investigated. The instruments are used: document analysis, participant observation, semi-structured interview, directed to the subjects involved in the process - parents, counselor, teachers and responsible for secretary the Municipal Education and Culture of the respective municipality. The generated data are discussed and interpreted in the light of the Applied Linguistics references, notably the Portuguese language research as an additional language, the studies on the intercultural approach and the Linguistic Policies, especially the language management. Considerations about the insertion of the invisible result from the research: the Haitian child promotes the dynamics of changes in the processes of language management and teaching-learning of Portuguese, in addition to making other children visible, erased by the monolingual / monocultural system.